2017
DOI: 10.1186/s13148-017-0421-8
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of AXL and risk of childhood asthma symptoms

Abstract: Background AXL is one of the TAM (TYRO3, AXL and MERTK) receptor tyrosine kinases and may affect numerous immune-related health conditions. However, the role for AXL in asthma, including its epigenetic regulation, has not been extensively studied.MethodsWe investigated the association between AXL DNA methylation at birth and risk of childhood asthma symptoms at age 6 years. DNA methylation of multiple CpG loci across the regulatory regions of AXL was measured in newborn bloodspots using the Illumina HumanMethy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 80 publications
0
9
0
Order By: Relevance
“…Epigenome-wide and targeted patterns have also been assessed recently using bloodspots. Gao et al conducted an epigenome-wide analysis using the HumanMethylation 450 array (a predecessor to the MethylationEPIC array) on infant bloodspot specimens and identified a relationship between the epigenetic pattern of a gene known to play a role in asthma and the risk of wheeze by age six [ 64 ]. Another group evaluated bloodspot DNA methylation profiles using the HumanMethylation 450 array and found evidence that gestational folic acid deficiency may influence risk for cleft palate through an epigenetic mechanism [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Epigenome-wide and targeted patterns have also been assessed recently using bloodspots. Gao et al conducted an epigenome-wide analysis using the HumanMethylation 450 array (a predecessor to the MethylationEPIC array) on infant bloodspot specimens and identified a relationship between the epigenetic pattern of a gene known to play a role in asthma and the risk of wheeze by age six [ 64 ]. Another group evaluated bloodspot DNA methylation profiles using the HumanMethylation 450 array and found evidence that gestational folic acid deficiency may influence risk for cleft palate through an epigenetic mechanism [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Innate immune response and inflammatory response play an important role in pathogenicity of swine EP. AXL receptor tyrosine kinase (AXL) regulates inhibition of toll-like receptors (TLRs)-mediated innate immune response and the DNA methylation of AXL at birth was associated with higher risk for asthma-related symptoms in early childhood [20]. C-C motif chemokine ligand 11 (CCL11), an inflammatory cytokine, was significantly related to increased risk of asthma in adults [21].…”
Section: Positive Selection Signature Related To Susceptibility To Swmentioning
confidence: 99%
“…In fact, prominent Th2 cytokines were less methylated in asthmatic patients, resulting in higher expression of these asthma-promoting mediators. Interestingly, also gender-specific methylation structures were found, as CpG hypermethylation of the receptor tyrosine kinase AXL in newborns blood was associated with wheeze at age 6 especially in girls [56]. Epigenome-wide association studies (EWAS) revealed consistently hypomethylated signatures driven by higher numbers of eosinophil, a granular cell type that is known to be centrally involved in allergic inflammatory processes [57].…”
Section: Epigenetic Influencesmentioning
confidence: 99%